FOOT POSTURAL DEVIATIONS IN FEMALE KATHAK DANCERS (International Journal of Physiotherapy, 2017)
Background: Kathak is a very complex dance form in which greater emphasis is laid on foot work thus putting substantial amount of stress over the feet. The purpose of this study was to investigate the foot postural deviations amongst the Kathak dancers.Methods: Screening of 40 Female Kathak Dancers was done for the study from Department of Dance, Punjabi University, Patiala on the basis of inclusion criteria. Subjects were assessed for Postural deviations via. Foot Posture Index, Medial Longitudinal Arch Angle, Navicular Drop, Rearfoot angle and Forefoot angle.Results: Percentile analysis of Foot Posture index scores suggested that a large population of kathak dancers (approx 92.5 %) have pronated feet. Most of the Kathak dancers showed increase in Rearfoot angle (approx. 90%), Forefoot angle (approx.75%) and Navicular drop (approx. 97%) and decrease in Medial Longitudinal Arch angle (approx. 95%). Analysis of Coefficient of Correlation suggested a significant positive relationship of Foot Posture Index scores with Rearfoot angle (r = 0.40, p= 0.0087), Navicular Drop (r = 0.62, p= < 0.0001) and Forefoot angle (r = 0.51, p=0.0007) and a significant negative correlation with Medial Longitudinal Arch angle (r = -0.42, p= 0.0059).Conclusion: From the observations, it can be concluded that with time kathak dancers start developing certain Postural Deviations at Foot which can lead to hyperpronation. These changes if not treated on time may lead to various degenerative changes in the Foot and Ankle thus leading to the instabilities and can also make them susceptible to foot and ankle injuries, shin pain, etc. Thus, the study recommends that the dancers should be educated and trained about the foot problems associated with kathak dance and their prevention.